ALTERNATIVE THEORETICAL FRAMEWORKS FOR HYBRID SANDWICH PANEL WITH INTERMEDIATE LAYER - Jauhar Fajrin (Jurnal Rekayasa Sipil (JRS-Unand), 2015)
A concept of hybrid sandwich panel with intermediate layer has been introduced previously that capable of improving load carrying capacity of composite sandwich panel. While the previous work employed numerical and experimental investigation, the current paper more focuses on developing the theoretical frameworks of the hybrid sandwich panel by using analytical model. The vocal point of the concept is introducing a new layer in between the skin and the core of a standard sandwich panel structure to form a hybrid structure. The paper begins with elaborating the basic concept of sandwich panel which includes the elastic and shear stresses in sandwich panel and followed by the deflection of sandwich panel. The next stage comprehensively highlights the theoretical concept of the hybrid sandwich panel. It was clearly shown through the developed theoretical frameworks that the incorporation of intermediate layer can substantially increase the flexural rigidity and stiffnesses which finally enhances the load carrying capacity of the new developed sandwich panel.Keywords : sandwich panel, hybrid concept, intermediate layer, analytical model.